Litomosoides pardinasi Notarnicola & Navone, 2011 (Filarioidea: Onchocercidae) parasitizing the rodent Abrothrix andina (Philippi, 1858) (Rodentia: Cricetidae) in san juan Province, Argentina - Castillo, Gabriel N. (2025)
Nematodes of the genus Litomosoides Chandler, 1931 are body cavity parasites of a wide variety of hosts including bats, marsupials and rodents. The present study documents the first record of Litomosoides pardinasi Notarnicola & Navone 2011 in the rodent Abrothrix andina (Philippi, 1858) in San Juan Province, Argentina. Male nematodes of L. pardinasiwere characterized by a right spicule with a heel-like structure and a cuticularized terminal cap. A left spicule with a handle longer than the lamina and four pairs of postcloacal papillae. Females presented a vulva that is posterior to the esophagus-intestine intersection. This study provides novel information on the parasitism of A. andina in Argentina, representing the first record of this species of nematode in this rodent in the country and the first mention for the province of San Juan.